A scleral melting after intraocular surgery - (:unkn) unknown (My University, 2005)
A 51-year-old male with a diagnosis of idiopathic uveitis underwent cataract surgery. After cataract surgery, cystoid macular edema developed which did not resolve with medical therapy. Vitrectomy was performed due to persistence of cystoid macular edema and severe condensation of the anterior vitreous. At postoperative 1 month, scleral melting was detected at sclerotomy side which was repaired with heterolog scleral grafting.
Keywords: Scleral melting; Uveitis; Vitrectomy